Assembly of Aminopropyltetrasiloxane Cu2+-Induced in Aqueous Solution - Tao, Lei (Asian Journal of Chemistry, 2013)
A Cu2+-induced vesicle phase was prepared from a mixture of 3-aminopropyltetrasiloxane and CuCl2 or Cu(NO3)2 in aqueous solutions. Cu2+ coordinated with 3-aminopropyltetrasiloxane resulting in the formation of molecular bilayers, because Cu2+ can firmly bind to the amino groups of 3-aminopropyltetrasiloxane which reduced the area of the head-group. In this system, no counter ions in aqueous solution exist because of the Cu2+-ligand coordination and the bilayer membranes are not shielded by salts. The vesicles were determined by transmission electron microscopy images and dynamic light scattering measurements.